Healthcare Workers' Compliance With Standard Precautions and Associated Factors in Bahir Dar Town, Ethiopia. (August 2022) - Mulat Endalew, Salie; Abebe Melake, Bealemlay; Geremew, Abraham; Baraki, Negga; Mengistu, Dechasa Adare; Sintie Alamirew, Tamagnu; Muche Temesgen, Liku; Mulugeta Demmu, Yohannes; Alemeshet Asefa, Yohanis; Deriba, Wegene; Alemu, Fekade Ketema; Ayele, Dinku Mekbib; et al.
Background: According to the literature analysis, the majority of the studies focused primarily on public health institutions. Although assessing the compliance of healthcare workers in private and public institutions would give comprehensive evidence on existing problems and appropriate prevention method, as a result, research on adherence to standard precautions are still required. Rely on existing research, to the best of the investigator's knowledge, compliance with standard precautions in hospitals of Bahir Dar town has not been assessed. Therefore, this study will contribute to narrowing these gaps and determining the scope of problems with standard precautions. Methods: An institution-based cross-sectional study design was conducted among 442 healthcare workers working in hospitals from June 10 to 30, 2021. A stratified random sampling technique was employed to select the study participants. Pre-tested and structured questionnaires and an observational checklist were used to collect the required data. The data were entered into EpiData and analyzed using SPSS version 22. Bivariate and multivariable analyses were used to assess the association between independent and outcome variables. Odd ratios at 95% CI were used to measure the strength of the association between the outcome and explanatory variables. Finally, a P -value of <.05 was considered as a cut-off point for statistical significance. Results: Of the 442 healthcare workers who participated in the study, 41% were compliant with standard precautions. Furthermore, 68.1% and 51.8% of the respondents had good knowledge and a positive attitude toward infection prevention, respectively. Consistent water supply availability (AOR = 1.92 and 95% CI = 1.63, 6.27), and access to infection prevention guidelines (AOR = 1.73 and 95% CI = 1.08, 2.77), and availability of personal protective equipment (AOR = 2.32 and 95% CI = 1.35, 3.98) were some of the factors significantly associated with health care workers' compliance. Conclusions: The current study found that only about two-fifths of the healthcare workers complied with standard precautions. The study suggests that there is a significant risk of developing an infection. Therefore, the concerned organizations; Bahir Dar Zonal Health Office, and respective sectors including Amhara Regional Health Office and the Federal Ministry of Health must take appropriate measures to improve the implementation of safety practices.